Positive Externality Analysis of the Existence of PT. Great Gaint Pineapple Company (PT GGPC) to the Socio-Economic and Environment of the Community Around the Factory - Luciana, Lady; Marselina, Marselina (Lafadz Jaya Publisher, 2023)
This research is to obtain an overview of whether the existence of PT Great Gaint Pineppel Company has an influence on the socio-economic and environmental conditions of the community around the factory, namely in Lempuyang Bandar Village. Data collection techniques used in this research are interviews, questionnaires, literature studies and observations. The results showed that the existence of PT Great Gaint Pineapple has an impact on employment in the community, increasing income in the community, reducing poverty levels marked by ownership of personal and residential facilities, and reducing crime rates by looking at crime cases in the community every year. Then for the value of positive externalities, the existence of PT Great Gaint Pineapple is categorized as high, which is 3,706 from the results of the questionnaire distributed to the people of Lempuyang Bandar village.